(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article discusses the features of affixation in the Ukrainian terminology of accounting and auditing standards, the derivational analysis of Ukrainian terms of accounting and auditing is implemented, derivational models are described.